The UN Incheon strategy Implementation and the Pakistani quagmire; ground realities - Shaista Habibullah; Muhammad Naveed Babur; Muhammad Osama; Muhammad Ehab Azim; Zara Khalid; Huma Riaz (Journal of the Pakistan Medical Association, 2022)
Abstract “Economic and Social Commission for Asia and the Pacific” (ESCAP) is the regional developmental arm of “United Nations” (UN). There are over 650 million persons with disabilities (PWDs) living in the region. In 2012, the members of the ESCAP, including Pakistan gathered and launched the new decade of PWDs from 2013 to 2022 adopting the Incheon Strategy to “Make the Right Real” for PWDs, which is based on the “Convention on the rights of Persons with Disabilities” (CRPD) and aims to accelerate the disability inclusive development with 10 measurable time-bound goals and targets. The year 2017 marked the mid-point of the decade, and a “Government Members Report on the Implementation of Incheon Strategy” was submitted to UN-ESCAP by the member countries.